Arguments and inference in reading: an intervention proposal at an elementary school - Zotaquira, Martha Cecilia; Sánchez, Reina Del Pilar (Uptc, 2021)
This study aims to answer the question of how to promote the inferential reading of argumentative texts through pedagogical practices in elementary school? One answer for fifth grade students at the Institución Educativa Saza de Gámeza, Boyacá, Colombia, Sede la Capilla, is through the design of flexible learning guides based on a classroom project that favors the processes of inferential reading and argumentative criticism. A didactic unit was designed which focused on strengthening inference in reading processes through argumentative elements to assertively identify and detect premises and conclusions. A qualitative methodological design was applied using a critical social approach and participatory action research institutional project in collaboration with the institutional project; Cultivo de Haba-Institución Educativa Saza. The pedagogical intervention provides methodological, relevant, and experiential strategies for reading comprehension.